2005
DOI: 10.1177/10883576050200040601
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cardiovascular Responses to Stressors in Individuals With Autism Spectrum Disorders

Abstract: Characteristics of persons with autism and other developmental disabilities may make this population especially vulnerable to the effects of stress. Prior research on stress and its measurement in this population is reviewed. Using a single-case multielement design, this study explores the feasibility of measuring cardiovascular responses to four stressors in 10 individuals (age 13 to 37 years) with autism and other developmental disabilities. Results suggest that assessing cardiovascular responses is a viable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…The Polar Vantage XL is a portable, wireless monitor with a rubber electrode transmitter that fastens to gel pads adhered on a child's chest, and a watch-like receiver. Polar heart rate monitors demonstrate good reliability and validity based on simultaneous comparisons with electrocardiogram data, which is the gold-standard for non-invasive methods of heart rate monitoring (Groden et al 2005;Kadish et al 2001). We did not measure heart rate for Connor and Jack because they demonstrated physical resistance to the heart rate monitor when it was introduced.…”
Section: Materials and Equipmentmentioning
confidence: 98%
See 1 more Smart Citation
“…The Polar Vantage XL is a portable, wireless monitor with a rubber electrode transmitter that fastens to gel pads adhered on a child's chest, and a watch-like receiver. Polar heart rate monitors demonstrate good reliability and validity based on simultaneous comparisons with electrocardiogram data, which is the gold-standard for non-invasive methods of heart rate monitoring (Groden et al 2005;Kadish et al 2001). We did not measure heart rate for Connor and Jack because they demonstrated physical resistance to the heart rate monitor when it was introduced.…”
Section: Materials and Equipmentmentioning
confidence: 98%
“…Heart rate has been used frequently to measure responses to sensory stimuli in children with autism (Goodwin et al 2006;Groden et al 2005), and has been shown to be a particularly sensitive measure of arousal in children (Soussignan and Koch 1985). Although individuals with autism demonstrate significant between-subject variability in heart rate, withinsubject variability of heart rate is small at baseline and within tasks, and increases as expected with physical exertion (Goodwin et al 2006;Groden et al 2005). The Polar Vantage XL is a portable, wireless monitor with a rubber electrode transmitter that fastens to gel pads adhered on a child's chest, and a watch-like receiver.…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…Children with ASD often have communicative impairments (both nonverbal and verbal), particularly regarding expression of affective states (DSM-IV-TR, American Psychiatric Association, 2000; Green et al, 2002;Schultz, 2005). These vulnerabilities place limits on traditional conversational and observational methodologies; however, physiological signals are continuously available and are not necessarily directly impacted by these difficulties (Ben Shalom et al, 2006;Groden et al, 2005;Toichi & Kamio, 2003). As such, physiological modeling may represent a methodology for gathering rich data despite the potential communicative impairments of children with ASD.…”
Section: Fig 1 Framework Overviewmentioning
confidence: 99%
“…The group sizes and the cardinality of participant age range of many studies on technology-assisted autism intervention are commensurate with our work when an individual-specific approach was used (Pioggia et al, 2005;Robins et al, 2005;Robins et al, 2004;Werry et al, 2001). The affective modeling was performed based on a large sample size of observations (approximately 85 epochs over 6 hours) for each child with ASD, which is comparatively more extensive than many other works (Groden et al, 2005;Pioggia et al, 2005;Robins et al, 2004 www.intechopen.com…”
Section: Participantsmentioning
confidence: 99%
“…Physiological signals, however, are not necessarily directly impacted by the difficulties in emotional expressions in people on the autism spectrum [81,285,286].…”
Section: Physiology-based Modeling Of Engagement During Naturalistic mentioning
confidence: 99%